Transformasi Bunyi Sehari-hari menjadi Struktur Musikal: Studi Penciptaan Komposisi Musik “Warung Si Mba" - Agustin, Rany Ismaya; Setiaji, Deden; Apriani, Arni (Jurnal Ilmu Sosial, Humaniora dan Seni, 2025)
This study explores the aesthetic potential of everyday sounds as the primary material in contemporary music composition, using the work “Warung Si Mba” as a case study. The composition employs a musique concrète and soundscape composition approach by incorporating authentic sound recordings from traditional coffee stalls—such as the sound of sipping coffee, clinking spoons, and distinctive vendor calls. Through techniques such as field recording, editing, and layering, these commonly overlooked sounds are transformed into a structured musical narrative imbued with social and cultural significance. The work does not merely document sounds but interprets the cultural context and social interactions embedded within the coffee stall as a communal space for everyday people. This sound exploration broadens the boundaries of contemporary music by utilizing non-traditional sonic materials and creating an auditory experience that is grounded, reflective, and contextually rich. The results demonstrate that the acoustic landscape of daily life can serve as a meaningful source for musical creation, offering artistic innovation while also functioning as social documentation and cultural critique.